Universal design for the workplace: ethical considerations regarding the inclusion of workers with disabilities - Doussard, Claire (Journal of business ethics, 2024)
This paper examines the ethical issues of the inclusion of workers with disabilities in the workplace with a cross-fertilization approach between organization studies, the ethics of care, and a movement from the field of architecture and design that is called Universal Design (UD). It explores how organizations can use UD to develop more inclusive workplaces, first by applying UD principles to workspaces and second by showing how UD implies an integrative understanding of inclusion from the workspace to the workplace. Moreover, this paper discusses the ethical challenges and complexities that this design practice faces in regard to its applicability to diverse organizations and industries. Finally, this paper demonstrates that inclusion requires abandoning any notion of a perfect, productive body and, therefore, recognizing our shared vulnerability and fundamental interdependence in the workplace.